2018
DOI: 10.1063/1.5016995
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical strain on optical properties of ZnO nanowire

Abstract: The main objective of this study is to investigate the influences of mechanical strain on optical properties of ZnO nanowire (NW) before and after embedding ZnS nanowire into the ZnO nanowire, respectively. For this work, commercial finite element modeling (FEM) software package ABAQUS and three-dimensional (3D) finite-difference time-domain (FDTD) methods were utilized to analyze the nonlinear mechanical behavior and optical properties of the sample, respectively. Likewise, in this structure a single focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…This change in refractive index will also influence DoF, as a strain condition yielding a higher refractive index can enable more coupling of light waveguided towards the NR ends. Insights from previous studies involving the NR’s intrinsic emission properties indicated that, under tension (compression), a smaller (larger) bandgap is measured relative to an unstrained case [ 30 , 31 , 32 , 33 ]. In other studies, an inverse relationship between the bandgap and refractive index of a semiconducting material has been shown [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This change in refractive index will also influence DoF, as a strain condition yielding a higher refractive index can enable more coupling of light waveguided towards the NR ends. Insights from previous studies involving the NR’s intrinsic emission properties indicated that, under tension (compression), a smaller (larger) bandgap is measured relative to an unstrained case [ 30 , 31 , 32 , 33 ]. In other studies, an inverse relationship between the bandgap and refractive index of a semiconducting material has been shown [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, strain-altered ZnO NRs have been shown to alter their Schottky barrier height [ 25 , 26 ] and electrical conductance [ 27 , 28 , 29 ]. Strain was also used to change the near band-edge emission of ZnO nanowires [ 30 , 31 , 32 , 33 ], to shift the lasing modes of ZnO microwires [ 24 ], and to alter the phonon frequencies of ZnO NR Raman modes [ 34 ]. These past studies demonstrated how optical signals emitted from the ZnO nanomaterial itself such as the band-edge, photoluminescence, and lasing emissions can be modulated by applying stress.…”
Section: Introductionmentioning
confidence: 99%
“…These properties, obtained in flexible and conformable fiber mats, make these materials highly interesting for various applications in sensing and light-emitting devices, bioimaging, and photo-cross-linking as well as in network and bendable microlasers. Upon engineering the strength of the ZnO/polymer interface through proper surface modifiers or cross-linking of the organic matrix, one could also aim to obtain effective strain and load transfer to the inorganic component, , a perspective highly interesting for opto-mechanical coupling, and to exploit the piezoelectric properties of NWs in the hybrid material.…”
Section: Discussionmentioning
confidence: 99%
“…As such, previous works have used mechanical strain to modify the resistance [21], near band emission [17,19,20,22], and Schottky barrier height [23,24] of ZnO NWs. Simulation studies based on the finite element method (FEM) and three-dimensional (3D) finite difference time domain (FDTD) have also reported that the optical properties of ZnO NWs, such as reflectance, transmittance, and absorptance, are dependent on the applied mechanical strain [25][26][27]. These previous efforts have demonstrated that the intrinsic optical properties of ZnO nanostructures can be controlled through the application of strain.…”
Section: Introductionmentioning
confidence: 99%